2006
DOI: 10.1002/ijc.22361
|View full text |Cite
|
Sign up to set email alerts
|

PPARγ inhibitors reduce tubulin protein levels by a PPARγ, PPARδ and proteasome‐independent mechanism, resulting in cell cycle arrest, apoptosis and reduced metastasis of colorectal carcinoma cells

Abstract: The nuclear transcription factor peroxisome proliferator-activated receptor-gamma (PPARc) has been identified as an important therapeutic target in murine models of colorectal cancer (CRC). To examine whether PPARc inhibition has therapeutic effects in late-stage CRC, the effects of PPARc inhibitors on CRC cell survival were examined in CRC cell lines and a murine CRC model. Low doses (0.1-1 lM) of PPARc inhibitors (T0070907, GW9662 and BADGE) did not affect cell survival, while higher doses (10-100 lM) of all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
56
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(63 citation statements)
references
References 59 publications
(73 reference statements)
7
56
0
Order By: Relevance
“…Two of these antagonists, T0070907 and BADGE, potentiated ERa proteolysis in case of co-treatment with TGZ while GW9662 did not. This potentiation could explain the cell growth inhibitory effects of these compounds recently reported in the T47D breast cancer cell line and colorectal carcinoma cells [53][54][55].…”
Section: Discussionmentioning
confidence: 99%
“…Two of these antagonists, T0070907 and BADGE, potentiated ERa proteolysis in case of co-treatment with TGZ while GW9662 did not. This potentiation could explain the cell growth inhibitory effects of these compounds recently reported in the T47D breast cancer cell line and colorectal carcinoma cells [53][54][55].…”
Section: Discussionmentioning
confidence: 99%
“…1C), a leading experimental chemopreventive compound against colon cancer that inhibits intestinal tumors in APC min mice (17). We expect that therapeutic concentration of FH535 can be achieved in mice because T0070907 was shown to reduce the metastasis of injected cancerous cells in mice (44) and GW9662 suppressed mice obesity induced by a high-fat diet (45).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the respective relationships between both tubulin and GJIC with metastasis of prostate/other cancers have been studied. For instance, the level of tubulin affects the metastasis of colorectal carcinoma cells [31]; and breakdowns of GJIC in a variety of cancer cells correlate their metastatic capacity [32-34]. Moreover, studies have also indicated that TUBB6 itself is functionally related with the metastasis of various cancers.…”
Section: Discussionmentioning
confidence: 99%